Evaluasi User Experience Pada Aplikasi Linkaja Menggunakan Metode User Experience Questionnaire (UEQ) - Reggy Ayunda Agustina; Muhamad Azrino Gustalika (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Rapid technological developments, increasingly complete with the presence of fintech. One of the developing fintech in Indonesia is E-Wallet. Several supporting applications for using E-Wallet include OVO, DANA, LinkAja, ShopeePay and GoPay. According to the results of research by the Daily Social, LinkAja is an E-Wallet that still has few users and has a low rating on the Google Play Store when compared to other E-Wallets. LinkAja users have submitted various complaints in the Google Play Store comments column. Apart from that, LinkAja users also felt other complaints, such as failed upgrades, inappropriate service, deducted balances, and so on. The complaints mentioned point to the quality of the system and services provided by LinkAja, while the high quality of the services provided affects the high level of user satisfaction. With various kinds of problems and complaints about LinkAja, it is necessary to evaluate the user experience so that LinkAja can improve the user experience. One model method for measuring user experience and will be used in this study is the User Experience Questionnaire (UEQ). This study succeeded in evaluating the LinkAja application using the User Experience Questionnaire (UEQ). This study resulted in measurements of each aspect such as Attractiveness (1.552), Perspicuity (1.667), Efficiency (1.225), Dependability (1.233), Stimulation (0.958) obtained a positive evaluation value while Novelty (0.125) obtained a neutral evaluation value, and the benchmark results showed aspects of Attractiveness, Perspicuity, Efficiency, Dependability get the